Development and pilot testing a communication simulation training for interpreters to improve pain communication between primary care providers and patients with limited English proficiency - Maichou Lor; Abby M. Hammes (Elsevier, 2023)
Context: Health disparities in patients with limited English proficiency are worsened due to scarcity of interpreter-focused communication interventions and trainings. Objectives: To develop a high-fidelity simulation training for interpreters to use a novel pain communication tool, i.e., Pain Assessment Information Visualization (InfoViz) Tool, and evaluate interpreters' implementation fidelity during a pilot study. Methods: This research methodology study involved training interpreters through high-fidelity simulations and assessing the implementation fidelity of 20 patient-provider visits in primary care clinics. Descriptive statistics were calculated for the assessment and fidelity. Debriefing interviews were conducted after the training and at the study completion. These were transcribed and analyzed using thematic analysis. Results: Four interpreters completed training, requesting an average of 2.5 practice simulation studies prior to assessment (M = 54 min, score: M = 95%). Interviews revealed two themes: positive experiences and suggestions for improvement. Interpreters averaged 83% for implementation fidelity for the 20 visits. Post-study interviews revealed positive experiences and the need for refresher training. Conclusion: The communication simulation training for interpreters is feasible, acceptable, and can ensure accurate use of the Pain InfoViz Tool during provider-patient communication. Innovation: We applied a InfoViz Tool in pain simulations and extended high-fidelity training to medical interpreting.